I need help simplifying both of these. thank you!
![I need help simplifying both of these thank you class=](https://us-static.z-dn.net/files/d62/02c63b986cac8217ac6268e4e59bbbb2.png)
![I need help simplifying both of these thank you class=](https://us-static.z-dn.net/files/d28/30d2b76b84d6687eda0077588e95de89.png)
The distributive property is your friend. It tells you ...
a(b + c) = ab + ac
It can also be used to simplify the product of binomials (or other polynomials).
(a +b)^2 = (a +b)(a +b) = a(a +b) + b(a +b) = a^2 +ab +ab +b^2
(a +b)^2 = a^2 +2ab + b^2 . . . . . . . worth remembering
1. (x -10)^2 -x(x +80) = (x^2 -20x +100) +(-x^2 -80x)
= -100x +100 . . . . . . simplified form
For the purposes of calculation, it can be easier to factor out 100:
= 100 (1 -x)
Then for x = 0.97
= 100(1 -0.97) = 100(0.03) = 3
___
2. (2x +9)^2 -x(4x +31) = (4x^2 +36x +81) -4x^2 -31x = 5x +81
For x = 16.2, this is ...
5(16.2) +81 = 81 +81 = 162
_____
The purpose of the attachment is to show the evaluation is correct.